Choice of method for fluid inflow liquidation - Олексюк, Микола Петрович; Васько, Ігор Станіславович; Юрич, Андрій Романович (Technology audit and production reserves, 2014)
The analysis of scientific articles and published industry data to generalize the problem of fluid inflow liquidation and develop the recommendations for choosing the optimal method of fluid ablation with accounting the conditions of its admission into the hole is conducted in the article. It is established that the widest practical application have the acquired expectations and weighting method and the "driller method". A generalized comparison of methods is obtained and the factors that affect the technological possibility of their implementation are established. The basic of which is the amount of fluid that entered the hole. The recommendations on their use depending on the conditions of inflows are developed. The results of the investigation can be used by drilling-engineers at inflow liquidation and professionals involved in the creation of intelligent decision support systems.